Prevalência e fatores de risco para sibilância recorrente em lactentes de 12 a 15 meses na cidade de Cuiabá-MT, Brasil - Juca, Sileyde Cristiane Bernardino Matos Povoas [UNIFESP] (2019)
Objectives: To evaluate the prevalence of recurrent wheezing in infants in the city of Cuiabá-MT. To identify the factors associated with wheezing in the life’s first year. To verify the temporal trend in the epidemiology of wheezing in infants’ life’s first year. To identify passive smoking in infants with recurrent wheezing by urinary cotinine. Methods: Cross-sectional study of infants’ population base from 12 to 15 months using the standardized questionnaire from the Estudio Internacional de Sibilancias en Lactantes (EISL). The parents and/or guardians answered to the questionnaire during the visits to the Basic Health Units for routine visits and/or immunization or during home routine visits performed by health agents. For the evaluation of the temporal trend, the results found were compared to those previously obtained by a study performed between 2009 and 2010 in the same center and using the same method. Passive smoking was evaluated by the cotinine’s dosage in a urine sample. Results: A total of 1,066 infants, mostly male gender (N=539, 50.6%) and white race (N=456, 42.8%) participated in the study. 476 (44.7%) infants who participated in the study had at least one episode of wheezing in the first year of life, with the beginning’s average age of 6.6 months (±3 months) and significant male’s gender predominance. The prevalence of occasional wheezing (OW, less than three episodes) and recurrent wheezing (RW, up to three episodes) was 21.1% and 23.5%, respectively, which being the last one significantly higher in male gender (62.9%). Frequent nocturnal awakening (28.3%), perception of lack of air by parents (52.2%), emergency room visits (72.9%), hospitalization for wheezing (39.8%), use of beta agonist (88.4%) and oral corticosteroid (63.0%) were significantly higher in RW. The medical asthmas diagnosis (16.8%) and pneumonia diagnosis (46.2%) were higher in infants with RW. The main risk factors associated with wheezing in the first year were: smoking during pregnancy (OR=2.93; 95%CI=1.63-5.26); family income less than R$ 800.00 (OR=2.23, 95%CI=1.03-4.62); use of antibiotics in the first year (OR=1.95, 95%CI=1.42-2.67); first episode of airway infection before three months of life (OR=1.78, 95%CI=1.20-2.65); pneumonia hospitalization (OR=1.72, 95%CI=1.20-2.25); having siblings with asthma (OR=1.68, 95%CI=1.04-2.71), among others. The comparison between the two studies (2009-10 vs. 2016-17) showed elevated rates: wheezing ever, 27.7% vs. 44.7%, p<0.00; WO, 15.0% vs. 21.1%, p<0.00; and RW, 12.7% vs. 23.5%, p<0.00; significant increase also occurred in medical asthma diagnosis (9.5% vs. 16.8%, p<0.00). The mean cotinine level found among passive smokers was 32.4±8.6 ng/ml and the prevalence of passive smoking was 32.8%, being significantly higher among wheezing infants compared to those not exposed infants (41.8 % vs. 24.3%; p<0.030), especially in RW (63.2% vs. 20.7%; p<0.001). Conclusions: The prevalence of wheezing and RW in infants in their life’s first year was high and there was a significant increase over the years, associated with increased morbidity. Some of the factors which were found associated with wheezing in the first year of life are also associated with the development of asthma in children and adolescents. The evaluation of urinary cotinine levels proved to be a good marker for assessing exposure to cigarette smoke.